Molecular mechanisms and multi-target therapeutic strategies of diabetic nephropathy: from pathogenesis to precision interventions - Gong, Jiahuan; Fang, Xingxing; Yao, Xinlei; Xue, Fei; Qi, Guangdong; Chen, Bingqian; Sun, Hualin (Frontiers in Pharmacology, 2025)
Diabetic nephropathy (DN) has become the primary cause of end-stage renal disease globally, and its epidemiological burden intensifies alongside the surging prevalence of diabetes. The pathogenesis involves complex interactions among metabolic dysregulation, oxidative stress, inflammatory responses, and fibrotic signaling pathways. Hyperglycemia drives renal injury through activation of the RAAS and accumulation of advanced glycation end products (AGEs), while aberrant activation of key signaling pathways such as TGF-β/Smad3 and NF-κB further promotes renal fibrosis. Current clinical diagnosis primarily relies on proteinuria and glomerular filtration rate indicators, yet their insufficient sensitivity for early renal injury leads to high underdiagnosis rates of nonproteinuric DN. Traditional therapy, centered on renin-angiotensin system blockers, can delay disease progression but fails to reverse renal fibrosis. Recent years have witnessed significant therapeutic breakthroughs. These include SGLT2 inhibitors improving glomerular hypertension via mechanisms independent of glucose-lowering, novel anti-inflammatory and anti-fibrotic agents such as nonsteroidal mineralocorticoid receptor antagonists targeting TGF-β/Smad3 pathway inhibition, and multi-target traditional Chinese medicine interventions offering comprehensive protection by regulating signaling networks like PI3K/Akt and AGE-RAGE. At the molecular level, research reveals that inflammation and immune dysregulation, oxidative stress and metabolic disorders, epigenetic modifications, and cellular structural and functional damage collectively form the intricate pathological network of diabetic nephropathy. Emerging technologies like nanodrug delivery systems, stem cell therapy, and gene editing show broad prospects for precise interventions targeting specific molecular pathways. Future research must integrate multi-omics technologies to deeply dissect disease heterogeneity, develop efficient biomarkers for early diagnosis, and optimize therapeutic efficacy through innovative drug delivery systems, while strengthening evidence-based validation of integrated traditional Chinese and Western medicine strategies. This approach will provide novel insights for the precise prevention and control of diabetic nephropathy.